2021
DOI: 10.3389/fneur.2021.714594
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment for Acute Stroke Patients With a Pre-stroke Disability: An International Survey

Abstract: Background: It is unclear what factors clinicians consider when deciding about endovascular thrombectomy (EVT) in acute ischemic stroke patients with a pre-existing disability. We aimed to explore international practice patterns and preferences for EVT in patients with a pre-stroke disability, defined as a modified Rankin score (mRS) ≥ 2.Methods: Electronic survey link was sent to principal investigators of five major EVT trials and members of a professional interventional neurology society.Results: Of the 81 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A study involving sequential hospital admissions with acute stroke has demonstrated that every point increase in the pre‐stroke mRS score was associated with an increase in the rate of length‐of‐stay, discharge destination, mortality, and complications (Quinn et al., 2017). In general, IVT is not considered the first choice for AIS patients with PSD before stroke because of their possibly high mortality rate (Quinn et al., 2017; Salwi et al., 2021). Previous studies have demonstrated increased odds of mortality, whereas there was no significant difference between patients with and without PSD in return to their pre‐stroke level of function, sICH, or any ICH (Gensicke et al., 2016; Karlinski et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study involving sequential hospital admissions with acute stroke has demonstrated that every point increase in the pre‐stroke mRS score was associated with an increase in the rate of length‐of‐stay, discharge destination, mortality, and complications (Quinn et al., 2017). In general, IVT is not considered the first choice for AIS patients with PSD before stroke because of their possibly high mortality rate (Quinn et al., 2017; Salwi et al., 2021). Previous studies have demonstrated increased odds of mortality, whereas there was no significant difference between patients with and without PSD in return to their pre‐stroke level of function, sICH, or any ICH (Gensicke et al., 2016; Karlinski et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In general, IVT is not considered the first choice for AIS patients with PSD before stroke because of their possibly high mortality rate (Quinn et al, 2017;Salwi et al, 2021). Previous studies have demonstrated increased odds of mortality, whereas there was no significant difference between patients with and without PSD in return to their pre-stroke level of function, sICH, or any ICH (Gensicke et al, 2016;Karlinski et al, 2014).…”
Section: F I G U R E 2 Continuedmentioning
confidence: 99%
“…There is substantial uncertainty on whether EVT should be performed in patients with preexisting symptoms/disability, and treatment practices are highly variable. 35 The most commonly used argument against treating these patients with EVT is that functional outcomes are often poor, especially when compared to patients without preexisting symptoms/disability. 36,37 Indeed, a post hoc analysis of the HERMES collaboration showed that clinical outcome at 3 months is worse in patients with mild preexisting disability (mRS score 1–2), but this held true both for the control and EVT arms.…”
Section: Discussionmentioning
confidence: 99%
“…In general, clinicians do not always consider EVT for eligible ischemic stroke patients with prestroke disability due to the fact that they were more likely to die ( 6 , 28 ). Our findings were in line with previous studies ( 28 ) that showed every point increase in prestroke mRS was associated with a higher risk of mortality ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, prestroke mRS ≥2 is relatively common among patients harboring acute ischemic stroke, with a reported frequency between 23.5 and 34.1% ( 4 , 5 ). Furthermore, an international survey has reported that the EVT practice for patients with prestroke mRS ≥2 is heterogenous, and the EVT decision largely depends on clinician opinions ( 6 ). Therefore, selecting optimal treatments is necessary for these patients to obtain timely and successful revascularizations and improved clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%